Modular and coordinated expression of immune system regulatory and signaling components in the developing and adult nervous system - Monzón-Sandoval, Jimena; Castillo-Morales, Atahualpa; Crampton, Sean; McKelvey, Laura; Nolan, Aoife; O’Keeffe, Gerard; Gutierrez, Humberto (Frontiers in Cellular Neuroscience, 2015)
During development, the nervous system is assembled and sculpted through a concerted series of neurodevelopmental events orchestrated by a complex genetic programme. While neural-specific gene expression plays a critical part in this process, in recent years, a number of immune-related signalling and regulatory components have also been shown to play key physiological roles in the developing and adult nervous system. While the involvement of individual immune-related signalling components in neural functions may reflect their ubiquitous character, it may also reflect a much wider, as yet undescribed, genetic network of immune–related molecules acting as an intrinsic component of the neural-specific regulatory machinery that ultimately shapes the nervous system. In order to gain insights into the scale and wider functional organization of immune-related genetic networks in the nervous system, we examined the large scale pattern of expression of these genes in the brain. Our results show a highly significant correlated expression and transcriptional clustering among immune-related genes in the developing and adult brain, and this correlation was the highest in the brain when compared to muscle, liver, kidney and endothelial cells. We experimentally tested the regulatory clustering of immune system genes by using microarray expression profiling in cultures of dissociated neurons stimulated with the pro-inflammatory cytokine TNF-alpha, and found a highly significant enrichment of immune system-related genes among the resulting differentially expressed genes. Our findings strongly suggest a coherent recruitment of entire immune-related genetic regulatory modules by the neural-specific genetic programme that shapes the nervous system.